Cover Image. Issue 9 (September 2015) - Cooper, Kimberly L.; Shapiro, Michael D.
<x xml:space="preserve">Abstract</x> COVER PHOTOGRAPH: Deployment of regulatory genes during gastrulation and germ layer specification in a model spiralian mollusk Crepidula. From Kimberly J. Perry, Deirdre C. Lyons, Marta Truchado‐Garcia, Antje H. L. Fischer, Lily W. Helfrich, Kimberly B. Johansson, Julie C. Diamond, Cristina Grande, and Jonathan Q. Henry. To be published in Volume 244, Issue 10 of Developmental Dynamics.